Intention to adopt tax e-filing system among self-employed taxpayers in Nigeria - Adebayo, Lamidi Wasiu (2016)
electronic system directly to the tax authority. This system is a great move towards replacing the manual system of filing tax returns in Nigeria. The main objective of this study is to investigate the determining factors influencing taxpayers’ adoption of the tax e-filing system. To achieve this objective, survey method is utilized where self-employed taxpayers in Lagos State of Nigeria was selected as respondent. The study utilized self-administered questionnaire in which two research assistants were employed to help in administering the questionnaire. The total number of 175 respondents’ opinion were utilized to analyze the perception of the taxpayers towards tax e-filing system. Multiple regression analyses was used to investigate the relationship between independent and dependent variables and to examine the most significant factor(s) influencing taxpayers’ intention to adopt the tax e-filing system in Nigeria. The study found that perceived usefulness (PU), perceived ease of use (PEOU), technology readiness and facilitating condition have positive relationship with intention to adopt the tax e-filing system. Study also indicate that PEOU is the most significant factor influencing taxpayers’ intention to adopt the tax e-filing system. Therefore, the study recommend that government should ensure the tax efiling system is easy and easily navigable and that they should make sure the aim of its introduction is achieved.